Chapter 5.17 The Emergence of the Research Management Profession in Australia - Campbell J. Thomson; Tania Tambiah; Mark B. M. Hochman (Emerald Publishing Limited, 2023)
The creation of a Unified National System of Higher Education in Australia ( https://en.wikipedia.org/wiki/Dawkins_Revolution ) in the late 1980s resulted in many new universities and significantly increased research funding for the sector. The result was the emergence of the modern Research Management Office (RMO) and eventually the establishment of the Australian Research Management Society (ARMS) to support the development of research management professionals in the region; including Singapore, New Zealand, Pacific Islands, and Papua New Guinea. In 2013, ARMS launched an accreditation program to recognise and develop careers in research management. There are now more than 3,500 ARMS members with nearly 30% only having been in the profession for less than 5 years. The role of ARMS in helping Research Managers and Administrators (RMAs) redefine their roles and upskill is ever important in growing the profession and its leaders.
10.1108/978-1-80382-701-820231051; 10.1108/978-1-80382-701-820231051; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262